FITTING THE SPECTRA OF PIONS, KAONS, PROTONS, AND ANTIPROTONS IN RELATIVISTIC CU + CU COLLISIONS (International Engineering Journal For Research & Development, 2021)
By the BRAHMS collaboration investigated the spectra of Pions, Kaons, protons, and antiprotons in relativistic Cu + Cu at an energy of =200 GeV/s at the rapidity values y=0 and y=3. It was found that with an increase in the centrality of collisions, the collective radial flux of particles increases and the freeze-out temperature decreases. 5 GeV / c <pt <2. 5 GeV / c, the yield of Pions and Kaons is suppressed than in p + p collisions at the same energy. In this work, the experimentally obtained particle spectra are fitted by the Levy function and the exponential function of the Boltzmann type. It is shown that the fitted spectra of Pions by the Levy function and the spectra of Kaons and protons with an exponential function describe the experimental data well.